Psychological Dynamics in Incarcerated Amphetamine Dependence: An Interpretive Case Study - Putu Diana Wulandari; Aritya Widianti; Ratih Saraswaty; Ni Made Irene Novianti Astaningtias (Bali Medical and Wellness Journal, 2025)
Introduction: Substance dependence among inmates presents complex psychological challenges often rooted in personal history and environmental factors. This study aims to identify and analyze the specific psychological dynamics of an inmate diagnosed with amphetamine dependence to provide a basis for effective intervention. Case Description: This study utilized a qualitative case study approach involving "IK," a 25-year-old male inmate at Penitentiary X with a history of early-onset substance abuse. Data were collected through in-depth interviews, observation, and psychological assessments, including Graphic Tests (BAUM, DAP, HTP), SPM, Wartegg, and TAT. The subject presented with severe anxiety, moderate depression, and profound feelings of guilt and inferiority, exacerbated by a history of parental divorce and the loss of his partner and child during incarceration. Discussion: The analysis reveals that the subject's amphetamine dependence functions as a maladaptive coping mechanism stemming from a dysfunctional family history and childhood trauma. The prison environment has further intensified his psychological distress, particularly anxiety and internal conflict regarding his inability to take responsibility. Despite possessing average intelligence, the subject exhibits emotional repression and a low fighting spirit, which are critical factors influencing his recovery potential. Conclusion: The psychological dynamics of inmates with amphetamine dependence are deeply intertwined with past traumatic experiences and unsupportive environments. Understanding these underlying factors is crucial for correctional facilities and mental health practitioners to design personalized rehabilitation programs that address not only the addiction but also the root psychological vulnerabilities.